Clinical correlates of serum 25-hydroxyvitamin D in Parkinson's disease. (3rd June 2022) - Barichella, Michela; Cereda, Emanuele; Iorio, Laura; Pinelli, Giovanna; Ferri, Valentina; Cassani, Erica; Bolliri, Carlotta; Caronni, Serena; Pusani, Chiara; Schiaffino, Maria Giulia; Giana, Angelica; Quacci, Elena; et al.
ABSTRACT: Background: Parkinson's disease (PD) patients have lower levels of serum 25-hydroxyvitamin D (25(OH)D) than the general population. Previous studies have suggested a negative association between 25(OH)D and clinical features of PD, but the data are inconsistent. Materials and Methods: We conducted a cross-sectional, observational study. Serum 25(OH)D, disease (Hoehn-Yahr stage [HY]) and clinical symptom (Unified Parkinson Disease Rating Scale [UPDRS]) severity and global cognitive functions (Mini-Mental State Examination [MMSE]) were studied in 500 consecutive PD patients not using vitamin D supplements. Information on sunlight exposure and dietary intakes (using a 66-item food frequency questionnaire) were also collected. A convenient sample of age and sex-matched community healthy controls ( N  = 100) was included as a control group. Results: PD patients had lower 25(OH)D serum levels than controls. Deficiency status (<20 ng/mL) was found in 65.6% of patients. 25(OH)D levels were independently correlated to sunlight exposure ( P  = .002) and vitamin D intake ( P  = .009). In multivariate models, using a Mendelian randomization approach, lower serum 25(OH)D was associated with more severe disease (HY, P  = .035), worse clinical symptoms (UPDRS Part-III total score [ P  = .006] and dopaminergic [ P  = .033] and non-dopaminergic subscores [ P  = .001]) and greater global cognitive function impairment ( P  = .041). Neither cognitive functions nor clinical features were associated with reduced intake of vitamin D and sunlight exposure. Conclusion: : Serum 25(OH)D was negatively correlated with disease and symptoms severity, as well as with global cognitive functions. Our study adds to the evidence that low 25(OH)D may affect the progression of PD negatively. Intervention studies in this area are required.